ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA MTS DI KABUPATEN CIANJUR PADA MATERI TEOREMA PYTHAGORAS - Tsiyaab Sundus Nurkhaeriyyah; Euis Eti Rohaeti; Anik Yuliani (IKIP Siliwangi, 2018)
This article is an analysis of the results of the test mathematical reasoning of grade IX students of Junior High School. The analysis focused to identify and recognize the qualities of difficulties experienced by students and to autheticate the mathematical reasoning level at the nineth grade students of junior high school in Kabupaten Cianjur. Qualitative descriptive is used as the research method. The samples brought for this research are 19 students of class IX in one of junior high school in Kabupaten Cianjur. Instrument test of reasoning ability of mathematic given as many as 6 items. The output of the analysis obtained based on written tests conducted is the degree of ability mathematical reasoning at students of junior high school in Kabupaten Cianjur is still classified low.